Application of the quadrature-difference method for solving Fredholm integro-differential equations - Jalius, Chriscella; Abdul Majid, Zanariah (IEEE, 2015)
Application of the quadrature-difference method for solving Fredholm integro-differential equations (FIDEs) is presented in this paper. The FIDEs will be discretized by using the combinations of Simpsons quadrature rule with finite difference. The method converts the FIDEs to a matrix equation which corresponds to a system of linear algebraic equations. The formulation and the implementation of the proposed method are also presented. Several numerical examples are presented to illustrate the performance of the proposed method.